2016
DOI: 10.1074/jbc.a115.664367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cholesterol reduction on receptor signaling in neurons.

Abstract: During preparation of this manuscript, an incorrect immunoblot was unintentionally inserted into the lower panel of Fig. 5B. This error has now been corrected and does not affect the results or conclusions of this work. However, for clarity of reference to the two panels of this figure, the last paragraph of the results on page 26387 should now read: "As shown in Fig. 5B, the hydrophobic membrane was rich in prenylated Ras (upper panels), whereas unprenylated Ras was extracted in the aqueous cytosolic fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Given the many roles of cholesterol in the CNS, it is clear that any disruption in the cholesterol supply to neurons can likely contribute to neurodysfunction. In agreement with human and animal studies, in vitro studies demonstrate that depletion of cholesterol has deleterious effects on neuronal function (Frank et al 2008; Fukui et al 2016; Thiele et al 2000; Valenza et al 2015). Taken together, this reveals a potential convergence point for cocaine use and HIV-1 Tat to accelerate neurocognitive impairment.…”
Section: Discussionsupporting
confidence: 74%
“…Given the many roles of cholesterol in the CNS, it is clear that any disruption in the cholesterol supply to neurons can likely contribute to neurodysfunction. In agreement with human and animal studies, in vitro studies demonstrate that depletion of cholesterol has deleterious effects on neuronal function (Frank et al 2008; Fukui et al 2016; Thiele et al 2000; Valenza et al 2015). Taken together, this reveals a potential convergence point for cocaine use and HIV-1 Tat to accelerate neurocognitive impairment.…”
Section: Discussionsupporting
confidence: 74%
“…Subgroup analysis suggests that ApoE e4 carrier status increases the response to intranasal insulin, implying an insulin-cholesterol relationship in this patient population (32). Furthermore, we and others have shown that knockdown or inhibition of cholesterol synthesis from neurons creates insulin resistance in those cells (33,34), suggesting a feed-forward connection between diabetes and AD.…”
Section: Discussionmentioning
confidence: 55%
“…In many cases, recruitment of the receptor into lipid rafts following activation or receptor activation within the raft itself is critical for the type and duration of downstream signaling and can lead to dramatically different cellular outcomes if the receptor is activated elsewhere. Additionally, disruption of lipid rafts through cholesterol depletion or other destabilizing agents has inhibitory effects, especially on RTK‐mediated signals, most notably the PI3K/Akt and ERK pathways in neurons (Fukui et al, ). These observations highlight the importance of plasma membrane compartmentalization and lipid raft integrity in maintaining signaling pathways important for cellular growth and survival.…”
Section: Influence Of Membrane Architecture On Neuronal Signalingmentioning
confidence: 99%